Objetivação de um currículo de educação física : entre o prescrito e o vivido - Assereuy, Janaina Esfalsini Figueira (2013)
This study seeks to understand the daily construction of a physical education curriculum, analyzing references and theoretical and methodological documents with which a participant and active teacher in a process of curriculum revision deal / mobilizes in his daily tasks for the objectification of the curriculum, what external and internal constraints had influence in the choices and ways of someone to perceive, explain and describe the organization and pedagogical treatment given to the content of this component in its curricular educational context of work. Support its analyzes in a sociological approach about the construction of the physical education curriculum and opts for a qualitative perspective, relying on an ethnomethodology. Uses the interpretive approach, expressing a methodological way that gives centrality to subject actions on the in the investigated process. The instruments for the data collection were: participant observation, interviews and document analysis. Investigates collective discussion; documents systematization; the proposals, actions and the cooperating teacher s classes. Notes the influence of external and internal constraints that potentiate the authorship and autonomy of the contributor teacher in building the curriculum experienced on daily physical education as generate tensions, struggles and conflicts. The present analyzes shows that the choices of the teacher, in the teaching project construction of physical education area, will be guided in a perspective that considers the experiences of students, as well as the reality of the community where she works